Wpływ turbulencji otoczenia na dynamikę zmian w organizacji - Wawrzynek, Łukasz (The influence of the turbulence of surroundings on the dynamics of changes in the organization, 2006)
The skills of the organization, consisting in immediate responses to changes generated in surrounding and anticipating future changes, is the feature conditioning its prosperity on the market. Quick answers, undertaken immediately define the elasticity of the organization i.e. the ability of quicker responses in comparison with the competition answers. Giving quick answers, in the form of immediately undertaken actions, results in giving answers at the earliest time before the competition can do the same. The dynamics of changes at the organization from one side depends from the turbulence of surroundings, that is from the attributive conditions of his functioning, but from the second side the dynamic of changes depends from the possessed by the organization abilities to make changes in quick succession.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 330-337